2012
DOI: 10.1210/en.2011-1921
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Placental Nutrient Transport in Mice Generated by in Vitro Fertilization

Abstract: More than 4.5 million children have been conceived by in vitro fertilization (IVF). Interestingly, singleton IVF offspring born at term have an increased incidence of low birth weight. The mechanism responsible for the lower birth weight is unknown, but alterations in placental function are possible. Hence, the goal of our study was to examine placental growth and function in mice generated in vivo or in vitro. To assess placental function, blastocysts were generated by IVF or produced by natural mating (contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
116
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(124 citation statements)
references
References 38 publications
5
116
2
1
Order By: Relevance
“…This phenomenon, that the differences in fetal weight observed at E13.5 disappear 6 days later (at E19.5), is in accordance with that reported by previous study (Bloise et al 2012), in which the relative IVF fetal weight to IVO controls is lowest at the mid-gestation stage. After that, differences in fetal weight between IVF and IVO embryos reduce gradually until they disappear.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This phenomenon, that the differences in fetal weight observed at E13.5 disappear 6 days later (at E19.5), is in accordance with that reported by previous study (Bloise et al 2012), in which the relative IVF fetal weight to IVO controls is lowest at the mid-gestation stage. After that, differences in fetal weight between IVF and IVO embryos reduce gradually until they disappear.…”
Section: Discussionsupporting
confidence: 93%
“…After that, differences in fetal weight between IVF and IVO embryos reduce gradually until they disappear. One plausible explanation is the compensatory effect due to the larger placentas in IVF groups compared with that in control groups (Bloise et al 2012). Indeed, we found evident placental overgrowth in IVF males and females.…”
Section: Discussionmentioning
confidence: 59%
“…Oocytes were obtained from superovulated C57Bl/ 6J female mice as described previously. 14,25 Briefly, female mice were injected with 5 IU of pregnant mare serum gonadotropin and 46 to 48 hours later with 5 IU of human chorionic gonadotropin (hCG). The following morning, oocytes were collected from the ampullae.…”
Section: Preimplantation Embryo Productionmentioning
confidence: 99%
“…Several studies in humans and animals have shown that in vitro fertilization (IVF) and embryo culture can be metabolically taxing on preimplantation embryos. Indeed, oxidative stress can have a considerable impact on embryo development and cultured preimplantation embryos show metabolic changes, 11 abnormal metabolic and ultrastructural configurations, 12 increased programmed cell death in cells in the inner cell mass, 13 abnormalities of placentation, 14 and altered expression of developmentally important genes. [15][16][17][18][19] Culture media and/or nonphysiological oxygen tension contribute to these adaptive changes to increased oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…This includes the periconceptional period, in which alterations to the trophectoderm, the progenitor pool to the placenta, can influence placentation days after the initial exposure (Kwong et al, 2000, Watkins et al, 2015, MacLaughlin et al, 2005, Tan et al, 2016a, Bloise et al, 2012. The placenta also can mediate sexually dimorphic outcomes, with perturbations in early development associated with female lethality (Tan et al, 2016b), while mid-late gestational exposures are largely associated with male-specific lethality (reviewed by Kalisch-Smith et al 2017a).…”
Section: Introduction To the Developmental Origins Of Health And Diseasementioning
confidence: 99%